Pablo Brescia y Oswaldo Estrada (eds.), McCrack: "McOndo", el Crack y los destinos de la literatura latinoamericana. Albatros Ediciones, Valencia, 2018; 270 pp. - Villarruel, Marco Antonio (El Colegio de México, 2020)
McCrack: "McOndo", el Crack y los destinos de la literatura latinoamericana.